Framework on how to leverage neglected and underutilized species (NUS) to improve nutrition - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
In 2019, operational framework was finalized and published/posted online in English, French, and Spanish. How-to notes and other guidance are in progress and will be finalized in 2020.